Ethnocultural Linguistic Study of the Concept of Nationality in the Sunda Wiwitan Community of Kampung Pasir Garut - Aditya Aditya; Adhi Yudha Nugraha; Muhammad Fikri Haikal; Vasra Revinda; Haenidar Aghseyna; Sudarto Sudarto (Universitas Galuh, 2025)
Local religion is one form of pluralism of beliefs in Indonesia. This is because of the long history of the formation of the Indonesian nation. Local religions are spread throughout Indonesia from Sabang to Merauke. One of the local religions in Indonesia is located in West Java Province, precisely in the Sundanese tribe, which is called the Sunda Wiwitan belief. Sunda Wiwitan is a religious belief that has existed since the ancient kingdom era. This belief upholds the values ​​of Sundanese customs and Sundanese culture. In one of its teachings, it is known as the terms kondisi cara ciri manusa kabangsaan and kondisi cara ciri bangsa kabangsaan. This concept describes the way the Sunda Wiwitan people live as fellow human beings and as part of a nation. This concept is adopted by the Sunda Wiwitan belief in the Kampung Pasir area in Samarang District, Garut Regency